Comparison of a low carbon steel processed by Cold Rolling (CR) and Asymmetrical Rolling (ASR): Heterogeneity in strain path, texture, microstructure and mechanical properties. (April 2021) - Muñoz, Jairo Alberto; Avalos, Martina; Schell, N.; Brokmeier, H.G.; Bolmaro, Raúl E.
Abstract: A low carbon steel was processed by Cold Rolling (CR) and Asymmetrical Rolling (ASR) at room temperature until 200 μm thickness reduction using multiple rolling passes of 25 μm. ASR process induced a soft curvature with a 45.7 mm length and 128.8 mm radius, while the CR process did not show any curvature. Materials showed differences in the strain path as well as in the texture and microstructure evolution, not only concerning the mode of deformation but also across the sheet thickness. The hardness and tensile tests indicated a higher strength after processing by ASR than CR for the same thickness reduction. Changes in dislocation densities and grain size were more pronounced in the surface neighborhoods of the material processed by ASR than the as-received (AR) and CR conditions, while the grain size and the dislocation densities of the CR material were more homogeneous across the sheet thickness. Synchrotron measurements allowed to build dislocations and crystal size distribution functions. These functions demonstrated that for the surface zones for ASR condition, high dislocation densities correspond to the grains developing rolling texture components. In contrast, the highest dislocations densities for the center zone formed inside the smallest crystals with shear texture orientations. By ASR, a heterogeneous material with hard surfaces was generated using multiple small thickness reductions in a narrow and thick sheet. In contrast, with CR, a homogeneous hardness increase was obtained throughout the sheet's thickness, avoiding curvature in the material. It was found that high and heterogeneous distributions of geometrically necessary dislocations (GNDs) across the sheet thickness were responsible for the ASR material additional hardening.